Forebrain-specific, conditional silencing of Staufen2 alters synaptic plasticity, learning, and memory in rats - Berger, Stefan; Bartsch, Dusan (Genome biology, 2017)
Dendritic messenger RNA (mRNA) localization and subsequent local translation in dendrites critically contributes to synaptic plasticity and learning and memory. Little is known, however, about the contribution of RNA-binding proteins (RBPs) to these processes in vivo.
Gesehen am 12.06.2018